Antiquities in the Collection of the Radziwiłł Family in the Wettin Era .......... 55 - Paliušytė, Aistė (Collecting Antiquities from the Middle Ages to the End of the Nineteenth Century: Proceedings of the International Conference Held on March 25-26, 2021 at the Wrocław University Institute of Art History, 2021)
The article examines the collections of antiques of one of the most influential families of the Grand Duchy of Lithuania – the Radziwiłł family, preserved in the residences of Nesvizh and Biała Podlaska in the first half and the middle of the 18th century. Different categories of artefacts are analysed and evaluated on the basis of the most unexplored inventories of the Radziwiłł family property, the correspondence of nobles and officials. The collection of the Radziwiłł family antiques continued the tradition of early modern collections of the Central European aristocrats. Their antique collections were among the largest in the Duchy, distinguished by a variety of artefacts. At the Radziwiłł family court, antiques were treated as curiosities, sources of history and instruments of cultural memory. They helped establish the identity of the family and create images of its power.